Place Memory Masyarakat pada Bangunan Cagar Budaya di Kota Palopo - Nurhijrah, Nurhijrah; Fisu, Amiruddin Akbar (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2019)
This study aims to determine the extent to which people can participate in efforts to preserve cultural heritage in the city of Palopo. Community participation is measured based on their cognition attachment to cultural heritage buildings in Palopo City. Cognition can be seen from how people can recall how the characteristics of cultural heritage buildings in Palopo City (place memory). Data were collected by interview technique and analyzed by the content analysis technique. The analysis results show that the form of place memory of the Palopo City community towards cultural heritage buildings can be categorized into the location of the building, the function of the building, the physical characteristics of the building. The attachment of the Palopo City community towards cultural heritage buildings is evidenced by the efforts to preserve. Therefore, it is hoped that the results of this study can be one of the considerations for the preservation of cultural heritage buildings in Palopo City.